2012
DOI: 10.1371/journal.pone.0040648
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Intestinal Inflammation by Yeasts and Cell Wall Extracts: Strain Dependence and Unexpected Anti-Inflammatory Role of Glucan Fractions

Abstract: Yeasts and their glycan components can have a beneficial or adverse effect on intestinal inflammation. Previous research has shown that the presence of Saccharomyces cerevisiae var. boulardii (Sb) reduces intestinal inflammation and colonization by Candida albicans. The aim of this study was to identify dietary yeasts, which have comparable effects to the anti-C. albicans and anti-inflammatory properties of Sb and to assess the capabilities of yeast cell wall components to modulate intestinal inflammation. Mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
86
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 100 publications
(96 citation statements)
references
References 67 publications
(76 reference statements)
10
86
0
Order By: Relevance
“…may also demonstrate biotherapeutic effect. Results of the latest study by Jawhara et al [16] confirm this line of thought. The authors screened a range of S. cerevisiae sp.…”
Section: Introductionsupporting
confidence: 52%
See 3 more Smart Citations
“…may also demonstrate biotherapeutic effect. Results of the latest study by Jawhara et al [16] confirm this line of thought. The authors screened a range of S. cerevisiae sp.…”
Section: Introductionsupporting
confidence: 52%
“…Results of this study may be a basis for obtaining bioactive b-glucans and mannoprotein preparations or elaboration of probiotic culture of increased content of cell wall structure polymers. The experimental data point that not only polymers isolated from cell wall of yeasts of Saccharomyces genus demonstrate health-promoting activity, but also the whole cells of these fungi [3,16,54].…”
Section: Yeasts Biomass Yield In Experimental Cultivationsmentioning
confidence: 97%
See 2 more Smart Citations
“…Such studies have included in vitro analysis of physiological traits (i.e. the ability to grow at body temperature, pseudo-hyphal growth, protease and phospholipase secretion) [22] and in vivo analysis in experimental models of infection/colonization [23,24]. These studies demonstrated that there are obvious differences in pathogenic potential of strains although the reasons for this are not yet understood.…”
mentioning
confidence: 99%